The Impact of Calcium Supplementation on Physiological Activity and Cherelle Wilt Reduction in Cocoa (Theobroma cacao L.) - Avianto, Yovi (Jurnal Biologi Tropis, 2025)
Cocoa production in Indonesia has been challenged by declining productivity due to various factors, including cherelle wilt. Cherelle wilt, a condition characterized by the premature dropping of cocoa cherelle, is attributed to hormonal imbalances, nutrient deficiencies, and abiotic stresses. Calcium, as an essential nutrient, plays a crucial role in plant growth and can help mitigate the incidence of cherelle wilt. This study aimed to investigate the efficacy of calcium application in enhancing fruit set and reducing cherelle wilt in cocoa trees. The research was conducted from August 2020 to September 2022 at PT Pagilaran's Segayung Utara cocoa plantation, utilizing the RCC70 clone. Calcium chloride (CaCl2) was applied at rates of 0, 100, 200, 300, and 400 grams per tree per year. Results indicated that calcium fertilization improved the physiological performance of cocoa trees, as evidenced by enhanced chlorophyll fluorescence (Fv/Fm) and photosynthetic rate. These physiological improvements led to increased flower and fruit production, as well as a reduction in the incidence of cherelle wilt, particularly at application rates of 200-400 grams per tree per year. Consequently, overall yield and productivity were significantly increased at these rates.